The ethics of crowdsourcing - McDonough Dolmaya, Julie (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Because crowdsourced translation initiatives rely on volunteer labour to support both for-profit and not-for-profit activities, they lead to questions about how participants are remunerated, how the perception of translation is affected, and how minority languages are impacted. Using examples of crowdsourced translation initiatives at non-profit and for-profit organizations, this paper explores various ethical questions that apply to translation performed by people who are not necessarily trained as translators or financially remunerated for their work. It argues that the ethics of a crowd-sourced translation initiative depend not just on whether the initiative is part of a not-for profit or a for-profit effort, but also on how the project is organized and described to the public. While some initiatives do enhance the visibility of translation, showcase its value to society, and help minor languages become more visible online, others devalue the work involved in the translation process, which in turn lowers the occupational status of professional translators.